Conclusion: Is a New ASEAN Way of Conflict Management Emerging? - Mikio Oishi (Springer Singapore, 2016)
This final and concluding chapter of the book recapitulates the findings of the seven case studies in previous chapters and provides comparative reflections on the manners in which contemporary conflicts in Southeast Asia have been or were managed. These reflections are made in terms of internationalisation of conflict, failure of conflict avoidance, incompatibility management and mediation regime. As a result, there are emerging new patterns of managing conflict in the ASEAN domain, which can be described as follows: To intrastate conflict, which is easily internationalised, an international solution is the most natural and effective approach. This solution involves various domestic, regional and international actors, who constitute a mediation regime and initiate, consolidate and continue peace process. Regional autonomy provides the best solution to ethnic conflict which occupies the main part of intrastate conflict. ASEAN’s enhanced capacity to influence the domestic behaviour of the government of its member state can be a useful instrument of conflict management. In interstate conflict, mechanisms to maintain or restore self-restraint in conflicting parties are in place to prevent or manage crisis. As long as crisis is kept under control, conflict’s fundamental incompatibility is largely amenable to dissolution through negotiation or is made relatively insignificant among other issues. Middle-term relationship management to be applied to conflicting parties plays an important role for short-term crisis management and long-term incompatibility management or settlement.